Housing in Ireland: philosophy, affordability and access - Drudy, P. J. (Statistical and Social Inquiry Society of Ireland, 2007)
This paper argues that Ireland?s housing problems stem in part from a particular philosophical orientation which supports the ?commodification? of housing and gives strong encouragement to private market provision of housing for sale, for rent and capital gain and less attention to housing need. The paper examines the extent and causes of house price increases over the last decade, it draws comparisons with a number of other indices and concludes that housing in Ireland is over-valued/over-priced. A number of other indicators suggest that many new and aspiring house buyers are experiencing problems of affordability and other difficulties. Increased housing debt is a matter of serious concern. The structure of the private rental sector is examined and legislation introduced in 2004 to deal with the problems experienced by tenants is assessed. The paper also provides a preliminary evaluation of the work of the newly-established Private Residential Tenancies Board. The extent of ?housing need? is examined as well as the record of social housing provision, including provision for a number of marginalised groups and by means of the private rented sector. The rationale for selling social housing at a discount while buying such housing at market prices is examined. A number of key principles and policy recommendations are suggested.
Read before the Society, 1 February 2007
Keywords: Housing; Housing policy; House prices; 314.15